THE USE OF SPEECH ACTS IN ANGNGARU OF MAKASSAR SOCIETY - Murni Mahmud (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
The Use of Speech Acts in Angngaru of Makassar Society.The objective of this research is to explore the use of speech acts in Angngaru. Through the framework of speech act Searle (1969), this paper focuses on exploring the types and functions of Angngaruin Makassar society. To gain data, Angngarutexts were collected and analyzedthrough the techniques of discourse analysis. To support the data analysis, some performances of Angngaru were observed. The performers of Angngaru were also interviewed. The results of the study show that Angngaruhas important roles in Makassar society. The types of speech acts were found in Angngaru such as representatives, directives, commissives, and expressives. The analysis of the types and functions in this language useremarsthe strong relationship between language and culture in a particular society.